Condition Monitoring of Piezoceramic Fibers During Joining by Forming. (2016) - Drossel, W.-G.; Wittstock, V.; Hensel, S.; Schmidt, M.
Abstract: Nowadays, piezoelectric transducers with sensor or actuator functionality are applied on the surface of components by bonding. New research activities enable a novel process chain for sensor integration in which piezoceramic fibers are integrated directly into the surface of metal sheets using joining by forming. Scope of the paper is to investigate a method for condition monitoring of the piezoceramic fibers during the joining process. Different test samples are prepared and studied by its inherent sensor function in terms of electrical impedance during various loads. As a result, a novel approach is presented for monitoring the preload status during the forming operation and detecting errors by electrical impedance spectroscopy. This method contributes to ensure a high-volume production.